Evaluation on building construction waste management practice in Kurdistan Region of Iraq - Agha, Mahmood Muhammed; Ayob, Mohd Fairullazi; Ibrahim, Mohd Shariffuddin (Kulliyyah of Architecture and Environmental Design (KAED) International Islamic University Malaysia Jalan Gombak 53100, Kuala Lumpur Malaysia, 2022)
In the construction industry, material waste contributes to a major problem, and it is vital to manage material waste. The main objective of this research was to determine the significant factors contributing to construction wastes in the Kurdistan region of Iraq, particularly in the city of Sulaymaniyah. The construction industry provides a foundation for future construction projects; thus, it is significant to avoid and eliminate the causes of material waste in the construction process. The study's objective is to investigate the practice of material waste in the building construction sector to motivate the performance of managing construction projects in Iraq's Kurdistan region. The survey questionnaire was the main technique used for conducting and collecting primary data from relevant governmental bodies and construction companies with a study sample of 50 respondents. The result of the analysis demonstrated that the conventional construction method was the most common method utilized for construction. Also, the result illustrated that the main sources and causes of material waste were weak strategy for waste minimization, lack of staff awareness of waste management practices, and poor materials storage system. The most wasteful materials, including formworks (from timber/wood), tile, sand, and concrete, were also determined. Apart from that, the result found that possible measures that might contribute to minimizing material waste included implementing effective site management and supervision techniques, employing skilled labour, and appropriate on-site material storage.